Clinical impact of the repair technique for posterior mitral leaflet prolapse: Resect or respect?. Issue 3 (11th January 2021) - Sakaguchi, Taichi; Hiraoka, Arudo; Totsugawa, Toshinori; Hayashida, Akihiro; Ryomoto, Masaaki; Sekiya, Naosumi; Chikazawa, Genta; Yoshitaka, Hidenori
Abstract: Background and Aim: Leaflet resection and chordal reconstruction are established repair techniques for posterior mitral valve (MV) prolapse. This study aimed to compare the clinical results of the resect and respect approaches, with a particular focus on MV hemodynamics. Methods: Overall, 291 patients who underwent elective MV repair for isolated posterior leaflet prolapse between 2012 and 2020 were enrolled. Patients who underwent leaflet resection alone were classified as the "resection" group ( n = 166), while patients who underwent neochordal replacement with/without limited leaflet resection were classified as the "respect" group ( n = 125). Early postoperative MV hemodynamics and midterm repair durability were compared between the groups. Results: The annuloplasty ring size was significantly larger in the respect group than in the resection group (31.0 ± 2.1 vs. 30.4 ± 2.0 mm, p = .028). The respect group showed significantly lower mean MV gradient (2.6 ± 1.1 vs. 3.0 ± 1.4 mmHg, p = .03) and larger effective orifice area (EOA) (1.86 ± 0.48 vs. 1.66 ± 0.47 cm 2, p < .001) than the resection group. Multivariable analysis identified the respect approach, younger age, female sex, larger ring size, and partial band as independent determinants of larger EOA. The rate of freedom from moderate or greater recurrent mitral regurgitation 5 years postoperatively was 90.9% in both groups. Conclusions: The respect approach allowed for a lower MV gradient and a larger EOA than the resection approach, which is possibly due to the capability of implanting a larger annuloplasty ring.